Working with young homeless people - Robinson, Phil (Jessica Kingsley Publishers, 2008)
What is youth homelessness? -- Characteristics of young homeless people -- A history of youth homelessness -- A geography of youth homelessness -- Something to do : education, training and employment -- Family: a help or a hindrance -- Friends and acquaintances: helping young people to maintain and rebuild social networks -- Drugs and alcohol : dealing with substance misuse -- Housing and support : working for sustainable futures -- The human factor : what works when responding to adolescent behaviour? -- The future of services for the homeless